Implementation of Population Policy Towards Indonesia’s Golden Vision 2045: Strengths and Future Challenges - Muhammad Cholifihani; Qori’atul Septiavin (International Publisher (YAPENBI), 2025)
This study aimed to analyze the advantages and drawbacks of Indonesia’s population policy within the framework of the National Long-Term Development Plan (RPJPN) 2025–2045. The objective was to examine how demographic management can contribute to realization of the Indonesia’s Golden Vision 2045. A qualitative research method was applied through a literature review, focusing on strategic themes such as optimizing the demographic bonus, controlling population growth, developing intermediate cities, and promoting social inclusion for vulnerable groups. The study drew on academic articles, policy documents, and official government reports, purposively selected to represent the most relevant and updated sources. The instrument used in this study was a document analysis matrix to categorize findings according to opportunities and challenges. The results indicated that the RPJPN 2025–2045 provided a strong strategic direction to harness demographic momentum by enhancing human capital and economic productivity. However, challenges were identified in the form of regional development disparities, unequal access to basic services, risks of uncontrolled urbanization, and potential increases in unemployment if education and employment sectors were not adequately prepared. This study concluded that strengthening local-level policy implementation, mainstreaming inclusive development, and fostering cross-sectoral synergy were essential for effective demographic management. The findings were expected to support the development of adaptive and sustainable population strategies that could ensure Indonesia’s demographic advantages were transformed into long-term national progress.